Assurance of climate risks: an analysis of accounting disclosure in the agricultural sector (Research, Society and Development, 2022)
The study aims to identify the existence of assurance on environmental disclosure of the risk of climate change in companies in the non-industrial, acyclical agricultural sector, listed in B3, in the period between 2016 and 2020. The empirical descriptive qualitative research, being used in the collection of data, the bibliographic and documentary research with consultations to the Annual Report (RA), Sustainability Report (RS), Reference Report (RR), Integrated Report (RI), Assurance Reports (RAs) and Opinions of Audit (PA) of the companies available on the websites of the companies themselves and in the information provided in B3. Climate change can affect agricultural production in different ways, in this sense, investors have demanded more quality information about ensuring the disclosure of climate risks. The results found indicate that 27.27% of the companies listed in the segment report climate risks. In these companies, assurance is focused on reporting risks related to: regulation, physical climate changes and market risks. It should be noted that only BRASILAGRO carried out the emissions inventory in the years 2017, 2018 and 2019/2020, these last years being presented together in a single report. The study contributes to signaling the disclosure and regulation of ensuring the reporting of climate risks in the agricultural sector and thus ensuring this information not only for investors but also for society.